Microbial community analysis involved in the aerobic - Zeng, Tian-jing (Water Science and Technology)
Recently, it has been found that biological phosphorus removal can be achieved in an aerobic/extended-idle (AEI) process using both glucose and acetate as the sole substrate. However, the microbial consortiums involved in glucose-fed and acetate-fed systems have not yet been characterized. Thus the aims of this paper were to investigate the diversities and dynamics of bacterial communities during the acclimation period, and to quantify polyphosphate-accumulating organisms (PAOs) and glycogen-accumulating organisms (GAOs) in the systems. The phylogenetic analysis showed that the microbial communities were mainly composed of phylum Proteobacteria, Bacteroidetes, Chlorobi and another six kinds of unclassified bacteria. Fluorescence in-situ hybridization (FISH) analysis revealed that PAOs and GAOs accounted for 43 ± 7 and 16 ± 3% of all bacteria in the glucose-fed system, and 19 ± 4 and 35 ± 5% of total bacteria in the acetate-fed system, respectively. The results showed that the conventional PAOs could thrive in the AEI process, and a defined anaerobic zone was not necessarily required for putative PAOs growth.